Essays on Discounting Behavior and Gambling Behavior - Lasse J. Jessen (Copenhagen Business School (CBS), 2016)
This thesis consists of three independent chapters on the elicitation of individual discount rates and on the estimation of gambling prevalence in Denmark. The first chapter, “Discount Rate Sensitivity to Background Consumption and Consumption Smoothing,” studies the sensitivity of individual discount rates with respect to background consumption and consumption smoothing. I use simulated choice data from standard decision tasks in time preference experiments and show that individual discount rates are sensitive to assumptions with respect to background consumption and consumption smoothing if the utility function is non-linear and exogenous. However, if discount rates and the utility function are elicited jointly, discount rates are robust to assumptions on time-invariant background consumption and consumption smoothing. The analysis clarifies mixed conclusions from previous studies and indicates which elicitation methods provide robust estimates of individual discount rates.
hdl:10398/9325
Keywords: 650